Factors associated with severe acute respiratory syndrome coronavirus-2 infection in Hohoe Municipality, Ghana: A case-control study - Sadat Ibrahim; Yussif Yakubu; Kwaku Appiagyei; Adjato Franklin Duncan Sylvester; Yahuza Sabit Tanko; Frank Baiden (PLoS ONE, 2026)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection was a major public health challenge globally and in Ghana. To prepare better for future pandemics, an evidence-based understanding of the determinants of coronavirus disease is essential to inform public health guidelines and surveillance. Thus, we identified the factors for SARS-CoV-2 infection in Hohoe Municipality. We conducted a facility-based, sex and age-matched (1:2) case-control study. Cases were persons with a laboratory-confirmed SARS-CoV-2 infection by Reverse Transcription Polymerase Chain Reaction (RT-PCR) or rapid antigen test, while controls tested negative with the same techniques. Data on sociodemographic, clinical, and exposure-related factors were collected through structured interviews. We employed a conditional regression model to establish the factors independently associated with SARS-CoV-2 infection using Stata version 17.0. All statistical tests were two-sided, and a p-value <0.05 in the final multivariate logistic model was considered statistically significant. A total of 234 participants were enrolled (78 cases, 156 controls). The mean age of the cases and controls was 39.7 (±14.6) and 39.4 (±14.4) years, respectively. Moderate/high levels of social interaction increased the odds of infection (aOR=3.00, 95% CI:1.05–8.56, p = 0.040). Having no underlying health condition (aOR=0.25, 95% CI:0.09–0.65, p = 0.004) and regular physical activity or exercise (aOR=0.18, 95% CI:0.04–0.70, p = 0.014) reduced the risk of infection. Public health interventions should therefore prioritize strengthening community awareness about the risks of close social interactions and the benefits of healthy lifestyles, including regular physical activity.